Let \( f: [0,\infty] \rightarrow \mathbb R\) be a non-decreasing continuous function. Show then that the inequality.

\[ \large (z-x) \int_y^z f(u) \, du \geq (z-y) \int_x^z f(u) \, du \]

holds for any \(0\leq x\leq y \leq z \).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestDefine \( g(x) \) as \( \dfrac{\int\limits_x ^z f(u)du}{z - x} \).

Show that \( g(x) \) is increasing - and you're done.

Indeed, \( g'(x) = \dfrac{\int\limits_x ^z f(u)du - f(x)(z - x)}{(z - x)^2}\)

Now see that \( f(u) \geq f(x)\) \( \forall \) \( u \in [x, z] \).

This means, \( \int\limits_x ^z f(u)du \geq \int\limits_x ^z f(x)du = f(x)(z - x) \) and \(g'(x) \geq 0 \)

Log in to reply

thanks sir sir what should be the approach while solving these types of problems.??

Log in to reply

Well, I noticed that the statement could be written in terms of a new function, \( g(x) \), because of the symmetrical way the statement is written.

If \( g(x) \) was increasing, then we would have what we wanted - and I showed that.

Log in to reply

Log in to reply

Log in to reply